Selection of adenovirus-specific and Epstein-Barr virus-specific T cells with major histocompatibility class I streptamers under Good Manufacturing Practice (GMP)-compliant conditions - Freimueller, Christine; Stemberger, Julia; Artwohl, Michaela; Germeroth, Lothar; Witt, Volker; Fischer, Gottfried; Tischer, Sabine; Eiz-Vesper, Britta; Knippertz, Ilka; Dörrie, Jan; Schaft, Niels; Lion, Thomas; et al. (Cytotherapy, 2015)
Despite antiviral drug therapies, human adenovirus (HAdV), cytomegalovirus (CMV) and Epstein-Barr virus (EBV) infections still contribute substantially to transplant-related death of patients after hematopoietic stem cell transplantation. Earlier clinical studies demonstrated successful adoptive transfer of magnetically selected CMV-specific T cells via removable, and thus Good Manufacturing Practice-compliant, major histocompatibility class I streptamers. Thus, the primary focus of the present study was the selection of HAdV-streptamer+ T cells, although in three experiments, EBV-streptamer+ T cells were also selected.Cells from leukaphereses of healthy donors were prepared in large (1-6 × 10(9)) and small (25 × 10(6)) cell batches. Whereas the larger batch was directly labeled with streptamers to select HAdV- and/or EBV-specific T cells (large-scale), the smaller batch was used to generate in vitro virus-specific T-cell lines before streptamer labeling for streptamer selection (small-scale). Isolation of HAdV- and/or EBV-specific T cells was performed with the use of the CliniMACS device.The purity of HAdV- and EBV-streptamer+ T cells among CD3+ cells, obtained from large-scale selection, was up to 6.7% and 44%, respectively. If HAdV- and EBV-streptamers were applied simultaneously, the purity of antigen-specific T cells reached up to 50.7%. A further increase in purity reaching up to 98% was achieved by small-scale selection of HAdV-specific T cells. All final products fulfilled the microbiological and chemical release criteria. Interferon-?-response indicating functional activity was seen in 6 of 9 HAdV and 2 of 3 EBV large-scale selections and in 2 of 3 HAdV small-scale selections.HAdV-streptamers were shown to be clinically feasible for few patients after the large-scale approach but for larger patient numbers if combined with EBV-streptamers or after the small-scale approach.
EVALuna2:19523